TINGKAT KEPUASAN KONSUMEN KLAPPERTAART DI KARTINI CAKE AND BAKERY MANADO - Meilany C. Wowor; Vicky R.B. Moniaga; Grace A.J. Rumagit; Charles R. Ngangi (Universitas Sam Ratulangi, 2015)
ABSTRACT The objective of this research is to measure the level of customer satisfaction by using an index of consumer satisfaction/ Customer (IKP). Data obtained by distributing a questionnaire of 30 respondents were measured using a Likert scale. In addition, the questionnaire in a test using data validity test and reliability of data. The research results showed that of the four aspects: the average value of the product customer satisfaction index of more than 0.753 that was satisfied. Aspects of the average value price index of consumer satisfaction more than 0.731 that was satisfied. Aspect that is where the value of the average customer satisfaction index of more than 0.7333 that was satisfied. Aspects of the service of the average value of consumer satisfaction index over 0.80 that was satisfied. Overall consumer Kartini Klappertaart was satisfied. Â Keywords: Consumer Satisfaction, Product, Price, Place, Services